2020
DOI: 10.1111/ner.13074
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and Safety of Dorsal Root Ganglion Stimulation for the Treatment of Chronic Pain: A Pooled Analysis

Abstract: Introduction Since it became available in the mid‐2010s, dorsal root ganglion (DRG) stimulation has become part of the armamentarium to treat chronic pain. To date, one randomized controlled trial, and several studies of moderate sample size and various etiologies have been published on this topic. We conducted a pooled analysis to investigate the generalizability of individual studies and to identify differences in outcome between chronic pain etiologic subgroups and/or pain location. Materials and Methods On… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 51 publications
4
36
0
2
Order By: Relevance
“…The number of complications observed in our retrospective analysis is consistent with the data of the pool analysis by Huygen et al These authors identified pain at the IPG pocket site (10.2%), lead fractures and migrations (11.8%), infections (5.1%) (26) as the most frequent complications. This rate may appear relatively high; but, it must be taken into account that this was still a young and technically completely new therapeutic procedure (41).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The number of complications observed in our retrospective analysis is consistent with the data of the pool analysis by Huygen et al These authors identified pain at the IPG pocket site (10.2%), lead fractures and migrations (11.8%), infections (5.1%) (26) as the most frequent complications. This rate may appear relatively high; but, it must be taken into account that this was still a young and technically completely new therapeutic procedure (41).…”
Section: Discussionsupporting
confidence: 91%
“…However, long‐term evidence of effectiveness is lacking. Also, the study of Huygen et al (26) was set up to present pooled data up to one‐year post‐permanent implant as this is the most common follow‐up period in published literature. There is an urgent need to collect and analyze long‐term data.…”
Section: Introductionmentioning
confidence: 99%
“…A pooled analysis by Huygen and colleagues found the most frequently reported complications of DRG stimulation were infections (5.1%), lead fractures (5.9%), lead migration (5.9%), temporary motor stimulation (4.7%), dural puncture (4.3%) and pain at IPG pocket site (10.2%). 6 There was no mention of itch or pruritus as a reported complication. A recent retrospective analysis by Kretzschmar and colleagues determined that their complications were consistent with those that Huygen et al had reported.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This highlights the importance of a comprehensive follow-up in detecting complications. It is worth noting that a pooled analysis of 217 patients from seven studies found the therapy to be effective and safe (4). And yet, in the public peer-review comments, the point is made that "rare complications are unlikely to show up in early prospective studies.…”
Section: To the Editormentioning
confidence: 99%